Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1128/aem.59.1.344-346.1993
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of membrane filters for recovery of legionellae from water samples

Abstract: The procedures currently used for isolating legionellae from environmental samples recommend filtration through a 0.2-,im-pore-size polycarbonate filter. In this study we evaluated the performance of 23 other filters composed of various materials and having various pore sizes. We prefer the 0.2-,im-pore-size Gelman Supor filter because of its high level of recovery, faster filtration rate, and ease of handling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 5 publications
1
23
0
1
Order By: Relevance
“…Nonetheless, if only particulate 234 Th activity needs to be measured, both SUPOR and GN6 filters provide viable options with PALL mixed cellulose ester filter being the easier of the two in terms of subsampling for punches. However in terms of trace metal analysis the SUPOR filters are found to be most appropriate because of its high level of recovery, faster filtration rate, low blanks, and ease of handling (Smith et al 1993;Cullen and Sherrell 1999;Kiene and Linn 1999 ommend using QMA filters when 234 Th is applied as a tracer of POC flux in the water column and to use SUPOR filters when 234 Th is being applied as a tracer of trace metal flux and cycling in the water column. In studies where 234 Th needs to be applied as a tracer for both POC and trace metals, the choice of filter can be solved by modifying the single filter holder McLane pumps into dual filter-holder pumps where one filter holder is loaded with QMA filter and the other filter holder is loaded with SUPOR filter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, if only particulate 234 Th activity needs to be measured, both SUPOR and GN6 filters provide viable options with PALL mixed cellulose ester filter being the easier of the two in terms of subsampling for punches. However in terms of trace metal analysis the SUPOR filters are found to be most appropriate because of its high level of recovery, faster filtration rate, low blanks, and ease of handling (Smith et al 1993;Cullen and Sherrell 1999;Kiene and Linn 1999 ommend using QMA filters when 234 Th is applied as a tracer of POC flux in the water column and to use SUPOR filters when 234 Th is being applied as a tracer of trace metal flux and cycling in the water column. In studies where 234 Th needs to be applied as a tracer for both POC and trace metals, the choice of filter can be solved by modifying the single filter holder McLane pumps into dual filter-holder pumps where one filter holder is loaded with QMA filter and the other filter holder is loaded with SUPOR filter.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the higher metal blanks associated with QMA filter make it a less than ideal filter for analyzing elements like 230 Th/ 231 Pa and Al. Based on previous work demonstrating the high level of recovery, faster filtration rate, low blanks, and ease of handling (Smith et al 1993;Cullen and Sherrell 1999;Kiene and Linn 1999) the TEI community had come to consensus to use polysulfone SUPOR filter as the filter of choice for TEI work during GEOTRACES intercalibration exercise. Because 234 Th can potentially be used to understand the cycling of trace metals in the upper ocean, it is imperative we test SUPOR filters along with QMA filters during this intercalibration exercise.…”
Section: Sampling Planmentioning
confidence: 99%
“…The use of e.g. polysulphone filter instead of nylon filter may raise the recovery rate of legionellas when samples are concentrated by filtration (Smith et al 1993). Another useful concentration method of samples may be centrifugation (Brindle et al 1987), especially if the samples are very dirty.…”
Section: Discussionmentioning
confidence: 99%
“…In our tests, we observed that when loading and unloading the PC filters in the Button Samplers it was important to ensure that the filters were not wrinkled. Smith et al (1993) noted difficulty with PC filters in terms of static charges and problems with folding and wrinkling during filter loading. It should be noted that previous studies have found that gelatin filters dried out over time and were of limited use for long-term sampling (Burton et al, 2005, Tseng andLi, 2005a).…”
Section: Pressure Drop Measurementsmentioning
confidence: 99%